Subsídios para monitoramento e manejo da resistência de Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) a inseticidas. - Silva, Leonardo Dantas da (2006)
The use of pesticides has been the major strategy to control the whitefly, Bemisia tabaci (Gennadius). The intensive use of these products has resulted in the development of whitefly resistance all around the world. Because of lack of studies in this subject in Brazil, the objectives of this research were: validate a bioassay technique to characterize the baseline susceptibility and evaluate the genetic variability of B. tabaci populations to some pesticides in Brazil. A residual contact bioassay by using foliar discs of Canavalia ensiformis L.. The effect of cotton and soybean plants on susceptibility of the rearing B. tabaci to acetamiprid, imidacloprid, thiamethoxan, chlorpyrifos, endosulfan and pyridaben was evaluated. Four whitefly populations, two from the Goiás state (GO-1and GO-2) e two from Bahia state (BA-1 and BA-2), were tested against a susceptible reference one (SusIAC). The foliar discs were treated by immersion on the chemical solutions and; then, they were transferred onto an agar-water solution in the bottom of a glass vial. Adult insect of unknown age and sex were transferred to the vials with treated foliar discs. Evaluations were performed after 24 h for endosulfan and 48 h for the other chemicals. The characterization of the baseline susceptibility of B. tabaci to the tested pesticides was more consistent when whiteflies were reared on cotton than on soybean plants. Significant differences in the susceptibility to pesticides were detected among B. tabaci populations. The population GO-2 was significantly less susceptible to tested pesticides than SusIAC, mainly to neonicotinoids. The most critical whitefly resistance situation was detected to thiamethoxan, followed by imidacloprid.